2021
DOI: 10.14302/issn.2639-3166.jar-20-3676
|View full text |Cite
|
Sign up to set email alerts
|

Vineyard Clusters Monitored by Means of Litterbag-NIRS and Foliar-NIRS Spectroscopic Methods

Abstract: There is currently a lack of rapid indirect analysis methods for the assessment of the effects of soil microbiota on vine production. Fifteen clusters of two Nebbiolo and Erbaluce varieties were identified in five vineyards belonging to a cooperative of winemakers in North West Italy, according to the differences in the NDVI index, as monitored by the Crop Monitoring OES system. The vineyards were surveyed in 2019 and the experimental monitoring of 75 vines was conducted in 2020. The first indirect method (Lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The models applied to the normalized and first derivative reflectance spectra were defined in a previous work (Baldi et al 2020) and resulted in 22 LBN-predicted variables. Moreover, the spectra of the subgroups were averaged and then fitted to the yield index, as already done in the work of Cugnetto et al (2021), although some outliers were identified beyond the t < 2 limit and were consequently excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The models applied to the normalized and first derivative reflectance spectra were defined in a previous work (Baldi et al 2020) and resulted in 22 LBN-predicted variables. Moreover, the spectra of the subgroups were averaged and then fitted to the yield index, as already done in the work of Cugnetto et al (2021), although some outliers were identified beyond the t < 2 limit and were consequently excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The first reference to a yield prediction from NIR spectra was achieved in a wine trial (Cugnetto et al 2021) in which an R 2 cross-validated value of 0.91 was found for Nebbiolo and 0.67 for Erbaluce vines. In a previous study on tomatoes (Baldi et al 2020), a linear regression of the yield on the % fingerprinting of the treatments with biofertilizer was observed in the NIRS of the litterbags, which reached an R 2 of 0.45, but when the NIRS fingerprinting of the leaves was added, the bilinear regression reached an R 2 of 0.95.…”
Section: Discussionmentioning
confidence: 99%
“…pulp, skins and seeds were divided and each berry was examined for pH using the Hamilton Double-Pore F electrode and by a bench refractometer for the degree brix, while a triplicate NIRS scan was applied to the pooled skins and seeds. The technological index was calculated as pH 2 * brix, whereas the phenolic index was expressed as the ratio of the non-extractable to the extractable phenols and was predicted from the NIR spectra according Cugnetto et al 29 .…”
Section: Journal Of Agronomy Researchmentioning
confidence: 99%